2020
DOI: 10.29309/tpmj/2020.27.10.4569
|View full text |Cite
|
Sign up to set email alerts
|

The consistency of the proximal perforator by using Color Doppler in anterolateral thigh flap.

Abstract: Objectives: The objectives of the study are to determine the consistency of the proximal perforator in terms of its presence and location prospectively using preoperative color doppler and per operative confirmation in patients requiring anterolateral thigh flap. Study Design: Descriptive Case Series. Setting: Department of Plastic Surgery at Jinnah Hospital Lahore. Period: From April 2017 to October 2017. Material & Methods: A total of 60 patients requiring anterolateral thigh flap were recruited for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to research conducted by Husnain Khan, the proximal perforator was consistently present as determined by Doppler in 85 percent of patients, indicating that 85 percent of patients have an AP over AK ratio of less than 0.45. 24 It is higher than 64% and 49% discovered by Kamita et al 26 and Yu et al, 27 respectively. When Khan H 24 compared gender to the consistent presence of the proximal perforator by Doppler, he found that there was no significant difference, indicating that Doppler is effective in ruling out the effect of gender.…”
Section: Discussionmentioning
confidence: 76%
“…According to research conducted by Husnain Khan, the proximal perforator was consistently present as determined by Doppler in 85 percent of patients, indicating that 85 percent of patients have an AP over AK ratio of less than 0.45. 24 It is higher than 64% and 49% discovered by Kamita et al 26 and Yu et al, 27 respectively. When Khan H 24 compared gender to the consistent presence of the proximal perforator by Doppler, he found that there was no significant difference, indicating that Doppler is effective in ruling out the effect of gender.…”
Section: Discussionmentioning
confidence: 76%